Syphilis Testing Among Female Prisoners in Brazil: Results of a National Cross-sectional Survey. (3rd March 2021) - Santana, Rosane da Silva; Kerr, Ligia; Mota, Rosa Maria Salani; Kendall, Carl; Justa Neto, Roberto da; Macena, Hermelinda Maia; Seal, David; Sousa, Alvaro Francisco Lopes; McFarland, Willi
Abstract: Brazil has the third largest prison population in the world and is also experiencing a high and rising rate of syphilis infection. To establish the gaps in syphilis testing, we examined data from a nationally representative sample of incarcerated women in Brazil. Data originated from a cross-sectional survey designed to represent all regions of Brazil ( N = 1, 327). Data were collected by Audio Computer-Assisted Self-Interview, including variables in several blocks or domains. 49.2% had a lifetime history of being tested for syphilis. Increased likelihood of syphilis testing was significantly associated with completed elementary education (odds ratio ajustado [AOR] 1.75, 95% confidence interval [CI] 1.28–2.40), completed high school or more (AOR 2.04, 95% CI 1.36–3.06), income below minimum wage (AOR 1.46, 95% CI 1.10–1.94), homelessness (AOR 1.83, 95% CI 1.21–2.76), having heard of the female condom (AOR 1.92, 95% CI 1.25–2.95), received a condom in prison (AOR 1.56, 95% CI 1.11–2.21) or in public health services (AOR 1.50, 95% CI 1.13–1.98), lifetime history of pregnancy (AOR 2.55, 95% CI 1.67–3.89), had a gynecological examination (AOR 1.73, 95% CI 1.05–2.83), and perceived they had some chance (AOR 1.61, 95% CI 1.17–2.20) or a big chance (AOR 1.89, 95% CI 1.31–2.73) that they were likely to have been infected with HIV before entering prison.